Tear matrix metalloproteinase-9 levels may help to follow a ocular surface injury in lagophthalmic eyes - Minaříková, Marcela; Fík, Zdeněk; Štorm, Josef; Helisová, Kateřina; Ferrová, Květoslava; Mahelková, Gabriela (PLoS One, 2022)
The preocular tear film is critically important for maintaining healthy ocular surface. In lagophthalmos, increased evaporation and tear film instability can occur. The level of tear matrix metalloproteinase 9 (MMP-9) is considered as a possible marker of ocular surface damage and inflammation. The aim of this study was to evaluate the possible usefulness of measuring tear film levels of MMP-9 in patients with lagophthalmos. Sixteen adult patients with unilateral lagophthalmos due to cerebellopontine angle mass surgery were included. Basic clinical examination including tear film osmolarity, degree of lagophthalmos, ocular surface sensitivity testing, corneal fluorescein staining, and tear break-up time (TBUT) were performed. Furthermore, tear MMP-9 quantification was performed and the values from lagophthalmic and contralateral healthy eye were compared. Possible correlations between tear MMP-9 levels and other parameters were analyzed. The Oxford score was higher in lagophthalmic eyes in comparison to healthy eyes. TBUT and corneal sensitivity were lower in lagophthalmic eyes. There was no difference in osmolarity between the two groups. Tear MMP-9 values were higher in lagophthalmic eyes. A higher MMP-9 value was associated with an increase in ocular surface fluorescein staining and a decrease of TBUT in lagophthalmic eyes. Tear MMP-9 may be used for monitoring ocular surface damage, contribute to early detection of inflammation progression and facilitate treatment adjustments.
Keywords: dospělí; Dry Eye Syndromes; zánět; Adult; poranění oka; lidé; Eye Injuries; Osmolar Concentration; Eyelid Diseases; fluorescein; Matrix Metalloproteinase 9; Tears; Fluorescein; Inflammation; osmolární koncentrace; matrixová metaloproteinasa 9; nemoci očních víček; syndromy suchého oka; slzy; Humans